Multilingualism and multiculturalism in an International Baccalaureate Diploma Programme with particular emphasis on supporting linguistic minority students. Issue 6 (2nd July 2020) - Lew, Shim
ABSTRACT: Multi/bilingual education has been found to have the potential to provide more equitable education for linguistic minority students; nevertheless, these students have not fully benefitted from it due to unequal power dynamics and Englishdominant language ideologies. While bilingual programmes in secondary schools remain extremely rare in the US, the Bilingual Diploma in the International Baccalaureate Diploma Programme offers a high school level bilingual curriculum and fosters heritage language education and multiculturalism. This study examines how advanced bilingual education in one International Baccalaureate Diploma Programme in a US high school served linguistic minority students' specific needs by establishing an institutional structure promoting heritage language learning, which significantly empowered those students by overcoming deficit-oriented ideologies.